Multicolor Photo‐Crosslinkable AIEgens toward Compact Nanodots for Subcellular Imaging and STED Nanoscopy. Issue 41 (12th September 2017) - Fang, Xiaofeng; Chen, Xuanze; Li, Rongqin; Liu, Zhihe; Chen, Haobin; Sun, Zezhou; Ju, Bo; Liu, Yifei; Zhang, Sean Xiao‐An; Ding, Dan; Sun, Yujie; Wu, Changfeng
Abstract: Aggregation induced emission (AIE) has attracted considerable interest for the development of fluorescence probes. However, controlling the bioconjugation and cellular labeling of AIE dots is a challenging problem. Here, this study reports a general approach for preparing small and bioconjugated AIE dots for specific labeling of cellular targets. The strategy is based on the synthesis of oxetane‐substituted AIEgens to generate compact and ultrastable AIE dots via photo‐crosslinking. A small amount of polymer enriched with oxetane groups is cocondensed with most of the AIEgens to functionalize the nanodot surface for subsequent streptavidin bioconjugation. Due to their small sizes, good stability, and surface functionalization, the cell‐surface markers and subcellular structures are specifically labeled by the AIE dot bioconjugates. Remarkably, stimulated emission depletion imaging with AIE dots is achieved for the first time, and the spatial resolution is significantly enhanced to ≈95 nm. This study provides a general approach for small functional molecules for preparing small sized and ultrastable nanodots. Abstract : Multicolor and ultrastable aggregation induced emission (AIE) dots are prepared by the photo‐crosslinking of oxetane‐substituted AIEgens. Due to the small sizes, good stability, and surface functionalization, the cell‐surface markers and subcellular structures are specifically labeled. Remarkably, stimulated emission depletion imaging with AIE dots is achieved for the first time, and the spatial resolution is significantly enhanced to ≈95 nm.